2016 Thailand Enterprise Survey : Country Highlights - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank Group conducted face-to-face interviews with top managers and business owners of 1,000 enterprises in Thailand from November 2015 through June 2016. The Enterprise Survey (ES) sample is representative of Thailand’s formal private sector. The ES covers several aspects of business environment along with measures of firm performance. The main highlights from the survey are: Thai firms underperform comparator economies in both annual sales and employment growth; female participation in ownership or management of the private sector is higher than in comparator economies; firms’ engagement in trade is lower in Thailand than in comparator economies; and political instability is most frequently cited as the biggest obstacle to private firms’ operations.